Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Diet of age-0 tarpon Megalops atlanticus near their northern range limit in the western Atlantic Ocean - Marvin M. Mace; Derek P. Crane; Matthew E. Kimball; Juliana M. Harding; Justin McNabb (Environmental Biology of Fishes, 2024)

The Role of Verbal Fluency in the Cerebellar Cognitive Affective Syndrome Scale in Friedreich Ataxia - Louise A. Corben; Eliza Blomfield; Geneieve Tai; Hiba Bilal; Ian H. Harding; Nellie Georgiou-Karistianis; Martin B. Delatycki; Adam P. Vogel (The Cerebellum, 2024)
Cerebellar pathology engenders the disturbance of movement that characterizes Friedreich ataxia (FRDA), yet the impact of cerebellar pathology on cognition in FRDA remains unclear. Numerous studies have unequivocally demonstrated the role of the cerebellar pathology in disturbed cognitive, language and affective regulation, referred to as Cerebellar Cognitive Affective Syndrome (CCAS), and quantified by the CCAS-Scale (CCAS-S). The presence of dysarthria in many individuals with ataxia, particularly FRDA, may confound results on some items of the CCAS-S resulting in false-positive scores. This study explored the relationship between performance on the CCAS-S and clinical metrics of disease severity in 57 adults with FRDA. In addition, this study explored the relationship between measures of intelligibility and naturalness of speech and scores on the CCAS-S in a subgroup of 39 individuals with FRDA. We demonstrated a significant relationship between clinical metrics and performance on the CCAS-S. In addition, we confirmed the items that returned the greatest rate of failure were based on Verbal Fluency Tasks, revealing a significant relationship between these items and measures of speech. Measures of speech explained over half of the variance in the CCAS-S score suggesting the role of dysarthria in the performance on the CCAS-S is not clear. Further work is required prior to adopting the CCAS-S as a cognitive screening tool for individuals with FRDA.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Does fluoride exposure impact on the human microbiome? - Gary P. Moran; Lina Zgaga; Blánaid Daly; Mairead Harding; Therese Montgomery (Toxicology Letters, 2023)

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Refining the risk of HTLV-1-associated myelopathy in people living with HTLV-1: identification of a HAM-like phenotype in a proportion of asymptomatic carriers - Daniel Harding; Carolina Rosadas; Sandra Maria Tsoti; Amanda Heslegrave; Molly Stewart; Peter Kelleher; Henrik Zetterberg; Graham P. Taylor; Divya Dhasmana (Journal of NeuroVirology, 2022)
Up to 3.8% of human T-lymphotropic virus type-1 (HTLV-1)-infected asymptomatic carriers (AC) eventually develop HTLV-1-associated myelopathy (HAM). HAM occurs in patients with high (> 1%) HTLV proviral load (PVL). However, this cut-off includes more than 50% of ACs and therefore the risk needs to be refined. As HAM is additionally characterised by an inflammatory response to HTLV-1, markers of T cell activation (TCA), β 2 -microglobulin (β 2 M) and neuronal damage were accessed for the identification of ACs at high risk of HAM. Retrospective analysis of cross-sectional and longitudinal routine clinical data examining differences in TCA (CD4/CD25, CD4/HLA-DR, CD8/CD25 & CD8/HLA-DR), β 2 M and neurofilament light (NfL) in plasma in ACs with high or low PVL and patients with HAM. Comparison between 74 low PVL ACs, 84 high PVL ACs and 58 patients with HAM revealed a significant, stepwise, increase in TCA and β 2 M. Construction of receiver operating characteristic (ROC) curves for each of these blood tests generated a profile that correctly identifies 88% of patients with HAM along with 6% of ACs. The 10 ACs with this ‘HAM-like’ profile had increased levels of NfL in plasma and two developed myelopathy during follow-up, compared to none of the 148 without this viral-immune-phenotype. A viral-immuno-phenotype resembling that seen in patients with HAM identifies asymptomatic carriers who are at increased risk of developing HAM and have markers of subclinical neuronal damage.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Characterisation of Sweet potato collusive virus (SPCV) isolates from sweet potato (Ipomea batatas) in Australia - Amit C. Sukal; Sandra Dennien; Dawit B. Kidanemariam; Karlah Norkunas; Eric Coleman; Robert M. Harding; Anthony P. James (Australasian Plant Pathology, 2022)
Sweet potato collusive virus (SPCV) is a member of the genus Cavemovirus , family Caulimoviridae , for which only one full-length genome sequence has been reported. SPCV was first detected in Australia in 2007 in two sweet potato accessions using the nitrocellulose membrane ELISA kit developed by the International Potato Centre (CIP). Infected plants were also shown to contain isometric virions of ~ 50 nm, typical of members of the genera Cavemovirus , Caulimovirus , Petuvirus and Soymovirus . We have now sequenced and characterised the complete genomes of the two SPCV isolates (designated SPCV-Aus1 and -Aus2) using a combination of next-generation sequencing and PCR/Sanger sequencing. The sequences of both isolates encode three major ORFs with a genome organisation typical of cavemoviruses. However, isolate SPCV-Aus2 possesses a considerably shorter genome length of 7275 bp compared to SPCV-Aus1 (7712 bp) and the only available full-length sequence from a Portuguese isolate (7723 bp; GenBank accession number NC_015328). Further, ORF 1 of SPCV-Aus2 is considerably shorter than the ORF 1 length of both SPCV-Aus1 and SPCV-Mad1. Phylogenetic and PASC analysis showed that SPCV-Aus1 is closely related to SPCV isolates from North and Central America, whereas SPCV-Aus2 clustered together with isolates from Portugal and Africa.

Longitudinal investigation of brain activation during motor tasks in Friedreich ataxia: 24-month data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louisa P. Selvadurai; Louise A. Corben; Martin B. Delatycki; Gary F. Egan; Nellie Georgiou-Karistianis (Brain Structure and Function, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Changes in stream food‐web structure across a gradient of acid mine drainage increase local community stability - Justin P. F. Pomeranz; Jeff S. Wesner; Jon S. Harding (Ecology, 2020)
Understanding what makes food webs stable has long been a goal of ecologists. Topological structure and the distribution and magnitude of interaction strengths in food webs have been shown to confer important stabilizing properties. However, our understanding of how variable species interactions affect food‐web structure and stability is still in its infancy. Anthropogenic stress, such as acid mine drainage, is likely to place severe limitations on the food‐web structures availabe, due to changes in community composition and body mass distributions. Here, we used mechanistic models to infer food‐web structure and quantify stability in streams across a gradient of acid mine drainage. Multiple food webs were iterated for each community based on species pairwise interaction probabilities, in order to incorporate the variability of realistic food‐web structure. We found that food‐web structure was altered systematically with a 32‐fold decrease in the number of links and a twofold increase in connectance across the gradient. Stability generally increased sixfold with increasing acid mine drainage stress, regardless of how interaction strengths were estimated. However, the distribution of the stability measure, s , for some impacted communities separated into clusters of higher and lower magnitude depending on how interaction strengths were estimated. Management and restoration of impacted sites needs to consider their increased stability, as this may have important implications for the recolonization of desirable species. Furthermore, active species introductions may be required to overcome the internal ecological inertia of affected communities.

Ecological processes mediate the effects of the invasive bloom-forming diatom Didymosphenia geminata on stream algal and invertebrate assemblages - J. P. Bray; C. Kilroy; P. Gerbeaux; F. J. Burdon; J. S. Harding (Hydrobiologia, 2020)

Differences in reported sun protection practices, skin cancer knowledge, and perceived risk for skin cancer between rural and urban high school students - Elizabeth S. Nagelhout; Bridget G. Parsons; Benjamin Haaland; Kenneth P. Tercyak; Kelsey Zaugg; Angela Zhu; Garrett Harding; Jeffrey Yancey; Jakob D. Jensen; Douglas Grossman; David W. Wetter; Yelena P. Wu (Cancer Causes & Control, 2019)

Characterisation of a subgroup IB isolate of Cucumber mosaic virus from Xanthosoma sp. in sub-Saharan Africa - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Benard O. Mware; Francesca Stomeo; James L. Dale; Anthony P. James; Robert M. Harding (Australasian Plant Pathology, 2019)

Molecular characterisation of a putative new polerovirus infecting pumpkin (Cucurbita pepo) in Kenya - Dawit B. Kidanemariam; Amit C. Sukal; Adane D. Abraham; Joyce N. Njuguna; Francesca Stomeo; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2019)

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

Development of an Educational Program Integrating Concepts of Genetic Risk and Preventive Strategies for Children with a Family History of Melanoma - Yelena P. Wu; Lisa G. Aspinwall; Elizabeth Nagelhout; Wendy Kohlmann; Kimberly A. Kaphingst; Sheila Homburger; Ryan D. Perkins; Douglas Grossman; Garrett Harding; Pamela Cassidy; Sancy A. Leachman (Journal of Cancer Education, 2018)

Characterization of an Australian isolate of taro bacilliform virus and development of an infectious clone - Dawit B. Kidanemariam; Amit C. Sukal; Kathy Crew; Grahame V. H. Jackson; Adane D. Abraham; James L. Dale; Robert M. Harding; Anthony P. James (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Remediation of a major acid mine drainage point source discharge restores headwater connectivity for a diadromous native fish - DP Gray; JS Harding; P Lindsay (New Zealand Journal of Marine and Freshwater Research, 2016)
Rivers receiving acid mine drainage (AMD) are frequently depauperate in fish and impacts may extend long distances downstream. AMD inputs may form chemical barriers for migratory species and isolate fish in unimpacted headwaters. We investigated the response of a diadromous fish, kōaro ( Galaxias brevipinnis ), to remediation of an AMD tributary in a 5th order river in New Zealand. A 2005 survey indicated limited recruitment of kōaro in the river likely due to the chemical barrier of AMD. By 2010, water treatment in the contaminated tributary had raised pH from a median value of 4.3 to 6 and reduced metals in the lower river, notably aluminium from a median of 2.48 to 0.41 mg/L. In 2012, kōaro density had increased by an order of magnitude relative to 2005. Furthermore, a greater proportion of juvenile fish were present. These results indicate that large‐scale remediation of discharges can reverse the impacts of AMD on fish migration.

Erratum to: Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Comparing total body lipid content of young‐of‐the‐year Steller sea lions among regions of contrasting population trends - Lorrie D. Rea; Brian S. Fadely; Sean D. Farley; Julie P. Avery; Wendy S. Dunlap‐Harding; Vicki K. Stegall; Carrie A. B. Eischens; Tom S. Gelatt; Kenneth W. Pitcher (Marine Mammal Science, 2016)
Steller sea lion ( Eumetopias jubatus ) young‐of‐the‐year ( YOY ) are nutritionally dependent upon their dam through the majority of their first year. Several indices of body condition were measured in YOY 1.5–9 mo of age captured in Southeast Alaska ( n = 122), the Gulf of Alaska ( n = 182), and the Aleutian Islands ( n = 38) to test the hypothesis that nutritional stress impacted the ability of adult female Steller sea lions to adequately nourish their late gestation YOY in the central Aleutian Islands in the early 2000s. Body mass (kg) and percent total body lipid content (% TBL ) increased with age in all three regions of Alaska that were sampled ( P P TBL measured by isotope dilution. The trend for Aleutian Island YOY to have larger body mass and larger body fat reserves are counter to what would be expected if dams were unable to adequately provision their late lactation YOY due to inadequate food availability in the central Aleutian Islands.

Complete genome sequence of a novel zantedeschia mild mosaic virus isolate: the first report from Australia and from Alocasia sp. - Dawit B. Kidanemariam; Adane D. Abraham; Amit C. Sukal; Timothy A. Holton; James L. Dale; Anthony P. James; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Early ocean distribution of juvenile Chinook salmon in an upwelling ecosystem - Jason L. Hassrick; Mark J. Henderson; David D. Huff; William J. Sydeman; Megan C. Sabal; Jeffrey A. Harding; Arnold J. Ammann; Eric D. Crandall; Eric P. Bjorkstedt; John Carlos Garza; Sean A. Hayes (Fisheries Oceanography, 2016)
Extreme variability in abundance of California salmon populations is often ascribed to ocean conditions, yet relatively little is known about their marine life history. To investigate which ocean conditions influence their distribution and abundance, we surveyed juvenile Chinook salmon ( Oncorhynchus tshawytscha ) within the California Current (central California [37°30′N) to Newport, Oregon (44°00′N]) for a 2‐week period over three summers (2010–2012). At each station, we measured chlorophyll‐ a as an indicator of primary productivity, acoustic‐based metrics of zooplankton density as an indicator of potential prey availability and physical characteristics such as bottom depth, temperature and salinity. We also measured fork lengths and collected genetic samples from each salmon that was caught. Genetic stock identification revealed that the majority of juvenile salmon were from the Central Valley and the Klamath Basin (91–98%). We constructed generalized logistic‐linear negative binomial hurdle models and chose the best model(s) using Akaike's Information Criterion ( AIC ) to determine which covariates influenced the salmon presence and, at locations where salmon were present, determined the variables that influenced their abundance. The probability of salmon presence was highest in shallower waters with a high chlorophyll‐ a concentration and close to an individual's natal river. Catch abundance was primarily influenced by year, mean fork length and proximity to natal rivers. At the scale of sampling stations, presence and abundance were not related to acoustic indices of zooplankton density. In the weeks to months after ocean entry, California's juvenile Chinook salmon population appears to be primarily constrained to coastal waters near natal river outlets.

Variable survival across low pH gradients in freshwater fish species - P. G. Jellyman; J. S. Harding (Journal of Fish Biology, 2014)
A series of 14 day experiments was conducted on five common New Zealand fish species (redfin bully Gobiomorphus huttoni , inanga Galaxias maculatus , brown trout Salmo trutta , longfin eel Anguilla dieffenbachii and koaro Galaxias brevipinnis ) to assess the effect of pH on survival and changes in body mass. No species survived in water of pH pH 4·5, G. maculatus larvae were also tested and had high mortality at this pH . Results suggest that adults are tolerant of low‐ pH waters; however, successful remediation of anthropogenically acidified streams will require an understanding of the susceptibility to low pH on different life cycle stages.

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Adaptive thermoregulation during summer in two populations of an arid‐zone passerine - B. Smit; C. T. Harding; P. A. R. Hockey; A. E. McKechnie (Ecology, 2013)
Heterothermy plays an important role in lowering the costs of thermoregulation in endotherms by reducing water and energy requirements. We tested predictions that birds in arid habitats should express fine‐scale variation in their thermoregulatory patterns as a function of prevailing climatic conditions. We assessed effects of air temperature ( T air ) and water vapor pressure deficit ( D ) on body temperature ( T b ) in free‐living White‐browed Sparrow‐Weavers ( Plocepasser mahali ) during summer in two arid habitats in the Kalahari Desert, South Africa, using data from a dry period at a hot, desert site ( n = 7 birds), and during a dry period ( n = 4 birds) and a wet period ( n = 5 birds) at a milder, semi‐desert site. The desert birds maintained a significantly higher set‐point T b (41.5° ± 0.2°C, mean ± SD) than semi‐desert birds (40.2° ± 0.2°C). During the warmest part of day (12:00–18:00 hours), T b increased significantly during periods of high T air and/or high humidity, and mean and maximum T b were up to 1.4° and 2.3°C, respectively, above normal levels. However, as T air increased, birds at the desert site maintained T b at or below set‐point levels for a greater proportion of the time than birds at the semi‐desert site. Birds at the desert site also expressed a greater magnitude of daily heterothermy (heterothermy index, HI = 2.4° ± 0.3°C, mean ± SD) than birds at the semi‐desert site: the latter population showed a greater magnitude of heterothermy during a dry period (HI = 2.1° ± 0.3°C) than during a wet period (HI = 1.6° ± 0.2°C). Birds continued foraging throughout the warmest part of the day, despite the fact that heat dissipation (percentage of time spent panting and wing‐spreading) increased significantly with increasing T air . Our findings reveal that populations can vary in their thermoregulatory responses in both space and time and suggest that small changes in T air can have significant effects on thermoregulation in free‐ranging desert birds, even when T air T b . These data have important implications for assessing vulnerability of species to climate change, suggesting that sensitivity should be assessed at the population, rather than species, level.

Use of bacterial communities to assess the ecological health of a recently restored stream - G Lear; P‐Y Ancion; J Harding; GD Lewis (New Zealand Journal of Marine and Freshwater Research, 2012)
We assess the utility of bacterial community data for providing an indication of stream health in a recently ‘restored’ urban stream. A community DNA fingerprinting technique was used to characterise the bacterial community within Okeover Stream, and a lesser impacted, nearby stream. No significant differences in bacterial community structure were detected between streams. However, further investigation revealed highly elevated levels of Zn, Pb and Cu associated with microbial biofilms in Okeover Stream and an increased abundance of genes encoding for bacterial resistance to Co, Zn and Cd. Benthic invertebrates were also sampled, confirming that despite recent attempts at stream restoration, the ecological health of the Okeover Stream remains poor. While the analysis of macroinvertebrate communities appeared to provide a more informative measure of overall stream health, we show that the targeted analysis of bacterial functional genes can be used to identify possible causes of declining ecological health.

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Initiation of embryogenic cell suspensions of taro (Colocasia esculenta var. esculenta) and plant regeneration - Pradeep C. Deo; Mary Taylor; Robert M. Harding; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Traditional Fisheries of Antongil Bay, Madagascar - P Doukakis; M Jonahson; V Ramahery; B.J De Dieu Randriamanantsoa; S Harding (Western Indian Ocean Journal of Marine Science, 2009)

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

Somatic embryogenesis, organogenesis and plant regeneration in taro (Colocasia esculenta var. esculenta) - Pradeep C. Deo; Robert M. Harding; Mary Taylor; Anand P. Tyagi; Douglas K. Becker (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Infectious exposure in the first year of life and risk of central nervous system tumors in children: analysis of day care, social contact, and overcrowding - N. J. Harding; J. M. Birch; S. J. Hepworth; P. A. McKinney (Cancer Causes & Control, 2009)

Identification and sequence analysis of potyviruses infecting crops in Vietnam - C. Ha; P. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Nanoscale Characterisation and Imaging of Partially Amorphous Materials using Local Thermomechanical Analysis and Heated Tip AFM - Ljiljana Harding; William P. King; Xuan Dai; Duncan Q. M. Craig; Mike Reading (Pharmaceutical Research, 2007)

Heightened stress response in primary fibroblasts expressing mutant eIF2B genes from CACH/VWM leukodystrophy patients - Liraz Kantor; Heather P. Harding; David Ron; Raphael Schiffmann; Christine R. Kaneski; Scot R. Kimball; Orna Elroy-Stein (Human Genetics, 2005)

Urocortin 1 expression in five pairs of rat lines selectively bred for differences in alcohol drinking - V. F. Turek; N. O. Tsivkovskaia; P. Hyytia; S. Harding; A. D. Lê; A. E. Ryabinin (Psychopharmacology, 2005)

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Molecular analysis of Fiji disease virus genome segments 5, 6, 8 and 10 - R. B. McQualter; P. Burns; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Analysis of variability in partial sequences of genomes of Tobacco yellow dwarf virus isolates - B. van Rijswijk; B. C. Rodoni; P. A. Revill; J. E. Thomas; J. R. Moran; R. M. Harding (Australasian Plant Pathology, 2004)

Sequence diversity of South Pacific isolates of Taro bacilliform virus and the development of a PCR-based diagnostic test - I. C. Yang; G. J. Hafner; P. A. Revill; J. L. Dale; R. M. Harding (Archives of Virology, 2003)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Manuka Honey Used to Heal a Recalcitrant Surgical Wound - R. Cooper; P. Molan; L. Krishnamoorthy; K. Harding (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Promoters derived from banana bunchy top virus DNA-1 to −5 direct vascular-associated expression in transgenic banana ( Musa spp.) - B. Dugdale; D. K. Becker; P. R. Beetham; R. M. Harding; J. L. Dale (Plant Cell Reports, 2000)

Banana bunchy top virus DNA-2 to 6 are monocistronic - P. R. Beetham; R. M. Harding; J. L. Dale (Archives of Virology, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Alteration of the quaternary structure of glutamate dehydrogenase from Clostridium symbiosum by a single mutation distant from the subunit interfaces - Jonathan L. E. Dean; H. Cölfen; Stephen E. Harding; David W. Rice; P. C. Engel (European Biophysics Journal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Handwipe sampling and analysis procedure for the measurement of dermal contact with pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos; R. G. Lewis (Archives of Environmental Contamination and Toxicology, 1996)

Handwipe Sampling and Analysis Procedure for the Measurement of Dermal Contact with Pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos (Archives of Environmental Contamination and Toxicology, 1996)

Organochlorine pesticides and polychlorinated biphenyls in the Arctic Ocean food web - B. T. Hargrave; G. C. Harding; W. P. Vass; P. E. Erickson; B. R. Fowler; V. Scott (Archives of Environmental Contamination and Toxicology, 1992)